Towards a digital twin based monitoring tool for ventilated patients - Hennigs, Carlotta; Sauer, Julia; Bigalke, Alexander; Hardel, Tim; Carbon, Niklas; Rostalski, Philipp (IFAC-PapersOnLine, 2024)
The complexity of processing and understanding the number of monitoring data available in the ICU is very demanding. The aim of this work is a model based sensor fusion approach for ventilated patients incorporating novel monitoring modalities such as surface electromyography and electrical impedance tomography. The data from various sensors are preprocessed and fused to estimate physiological parameters. As a result, a graphical user interface is developed to present the processed data generating an overview of the past and current patients' status to the clinical user in a compact form. In conclusion, the proposed concept and demonstrator of a monitoring tool provide a first approach to collect, fuse, and visualize various measurements of ventilated patients and form the basis for a medical digital twin for respiratory therapy.
CRIS-Team Scopus Importer:2024-12-13
Keywords: digital twin; graphical interface; mechanical ventilation; monitoring; sensor fusion